Learning From Success or Failure? – Positivity Biases Revisited - Harada, Tsutomu (Frontiers in Psychology, 2020)
The purpose of this study was to reexamine positivity learning biases through a Q learning computation model and relate them to behavioral characteristics of exploitation and exploration. It was found that while the positivity learning biases existed in the simple asymmetric Q learning model, they completely disappeared once the time-varying nature of learning rates was incorporated. In the time-varying model, learning rates depended on the magnitudes of success and failure. The corresponding positive and negative learning rates were related to high and low performance, respectively, indicating that successes and failures were accounted for by positive and negative learning rates. Moreover, these learning rates were related to both exploitation and exploration in somewhat balanced ways. In contrast, under the constant learning parameter model, positivity biases were associated only with exploration. Therefore, the results in the time-varying model are more intuitively appealing than the simple asymmetric model. However, the statistical tests indicated that participants eclectically selected between the asymmetric learning model and its time-varying version, a frequency of which differed across participants.